MitoRibo-Tag Mice Provide a Tool for In Vivo Studies of Mitoribosome Composition - Busch, Jakob D. (Cell Rep, 2019)
Mitochondria harbor specialized ribosomes (mitoribosomes) necessary for the synthesis of key membrane proteins of the oxidative phosphorylation (OXPHOS) machinery located in the mitochondrial inner membrane. To date, no animal model exists to study mitoribosome composition and mitochondrial translation coordination in mammals in vivo. Here, we create MitoRibo-Tag mice as a tool enabling affinity purification and proteomics analyses of mitoribosomes and their interactome in different tissues. We also define the composition of an assembly intermediate formed in the absence of MTERF4, necessary for a late step in mitoribosomal biogenesis. We identify the orphan protein PUSL1, which interacts with a large subunit assembly intermediate, and demonstrate that it is an inner-membrane-associated mitochondrial matrix protein required for efficient mitochondrial translation. This work establishes MitoRibo-Tag mice as a powerful tool to study mitoribosomes in vivo, enabling future studies on the mitoribosome interactome under different physiological states, as well as in disease and aging.